2011
DOI: 10.3109/17453674.2011.584209
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary leg lengthening with a motorized nail

Abstract: Background and purposeIn the last decade, intramedullary limb lengthening has become a viable alternative to traditional external systems. We retrospectively analyzed the use of an intramedullary motorized nail (Fitbone) in a consecutive series of 32 patients.Patients and methodsDuring the period September 2006 to December 2008, 32 consecutive patients with a median age of 17 (IQR: 15–19) years were treated with a fully implantable, motorized intramedullary lengthening device (Fitbone). The median leg length d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
90
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 20 publications
(45 reference statements)
13
90
0
2
Order By: Relevance
“…When comparing the accuracy of other methods of lengthening, we found that other intramedullary devices presented with more difficulty in controlling the rate of distraction, resulting in premature or delayed consolidation [16,[20][21][22]35]. Kenawey et al [20] reported an overall incidence of complications of 33%, of which the most important was insufficient bone regenerate (21%) and nine runaway nails.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…When comparing the accuracy of other methods of lengthening, we found that other intramedullary devices presented with more difficulty in controlling the rate of distraction, resulting in premature or delayed consolidation [16,[20][21][22]35]. Kenawey et al [20] reported an overall incidence of complications of 33%, of which the most important was insufficient bone regenerate (21%) and nine runaway nails.…”
Section: Discussionmentioning
confidence: 89%
“…For the past 10 years, the only FDA-approved intramedullary lengthening device has been the Intramedullary Skeletal Kinetic Distractor (ISKD) (Orthofix Inc, Lewisville, TX, USA). However, intramedullary lengthening is associated with complications, including premature or delayed consolidation with difficulty in controlling the rate of distraction, implant breakage, and mechanical failure [9,16,[20][21][22]35].…”
Section: Introductionmentioning
confidence: 99%
“…2 cm to max. 17.4 cm) for Ilizarov ring fixators (IRF) [48,57,58] and intramedullary nails [16,46,50,[59][60][61][62][63][64] and around 2.5-3 cm (min. 8 mm to max.…”
Section: Indications For Leg Lengtheningmentioning
confidence: 99%
“…There seems not to be a difference between femoral and tibial lengthenings, not between congenital and acquired problems but higher age, severity of deformity, unilateral fixation and amount of acute correction may have some additional negative impact [13,154]. The figures for complications according to Paley [22] are biased, since IRF and TSF are commonly used for more complex cases: they range from 46 to 72 % for external fixation [13,17,22], up to 60 % for LON [60], are around 29 % [16,49] for Albizzia nails, 31-50 % [51,55] for ISKD and 12.5-27 % [56,63] for Fitbone nails.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…This technique allowed them to remove the external fixator early, but healing still occurred at 48 days/cm. Healing rates following lengthening over an intramedullary nail are reported between 37 and 48 days/cm [9,11]. Future comparative studies are necessary to evaluate outcomes of these techniques relative to the longitudinal corticotomy technique described in the our study.…”
Section: Discussionmentioning
confidence: 99%